Variability in case fatality rate risk due to Covid-19 according to health services provider in Mexico City hospitals - Carmen García-Peña; Omar Yaxmehen Bello-Chavolla; Roberto Carlos Castrejón-Perez; Luis David Jácome-Maldonado; Luis Raymundo Lozano-Juárez (Instituto Nacional de Salud Pública, 2022)
Objective. To describe differences in Case Fatality Rate (CFR) for Covid-19 among healthcare subsystems in Mexico City between March and December 2020. Materials and methods. This is a retrospective secondary data analysis from the National Epidemiological Surveillance System data of Covid-19 cases. Information about health provider institutions was retrieved from the Catalogue of Health Establishments (CLUES). Logistic regressions were fitted to determine the association between health subsystems and mortality associated to Covid-19. The analyses were divided between hospitalized and ambulatory patients. Results. The probability of dying from Covid-19 was higher among those treated at Instituto Mexicano del Seguro Social (IMSS) (Hospitalized:OR=5.11, Ambulatory:OR=36.57), Instituto de Seguridad y Servicios Sociales de los Trabajadores del Estado (ISSSTE) (Hospitalized:OR=2.10, Ambulatory:OR=9.19), Secretaría de Salud (SS) (Hospitalized:OR=1.94, Ambulatory:OR=5.29) or other public institutions (Hospitalized: OR=1.70, Ambulatory:OR=9.56) than in those treated in private institutions. Conclusions. Differences in healthcare quality and access between health subsystems are profound. It is imperative to increase the capacity and quality of the different health subsystems to improve health outcomes.